2014
DOI: 10.1590/s1516-14392014005000096
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cobalt Rich Zn-Co alloy Coatings from Citrate Bath

Abstract: Zn-Co alloy coatings were produced on carbon steel, at room temperature, from citrate baths

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
13
0
3
Order By: Relevance
“…This result can be related to the metallic oxide and hydroxides that were produced on the electrode surface during metal deposition process, due to the interface alkalization caused by the water and O 2 reduction reactions 41,42 . Table 2, in which the Co content in these coatings was about four times higher than the Ni content.…”
Section: Microstructural Characterization Of the Coatingsmentioning
confidence: 97%
“…This result can be related to the metallic oxide and hydroxides that were produced on the electrode surface during metal deposition process, due to the interface alkalization caused by the water and O 2 reduction reactions 41,42 . Table 2, in which the Co content in these coatings was about four times higher than the Ni content.…”
Section: Microstructural Characterization Of the Coatingsmentioning
confidence: 97%
“…There is also literature available that addresses Zn alloy deposited from citrate baths. Garcia et al plated Zn‐Co alloy films on carbon steel at 25 ο C from citrate‐added baths. The researchers found that the current density and a sodium citrate complexing agent influenced the deposition process of the Zn‐Co alloy.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the hydrogen deposition and stabilize the plating baths, alkalis and complexing agents (e.g., acetate and citrate) were added into the baths for ideal Zn, Zn‐Ni, and Zn‐Ni composite electroplating. According to the above results, the corrosion‐resistant properties such as uniformity, thickness, and the mechanical hardness of the plated films were also improved . To fill this gap in information, a research study was conducted to study Zn‐Ni alloy deposition in different operating conditions and levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are several works concerning the use of alternative, environmentally-friendly electrolytic baths, that can be as efficient as cyanide ions in producing the metallic coatings 4,[6][7][8][9][10] . Among the environmentally friendly electrolytes currently used, citrates, gluconates, sulfamates, tartrates and glycinates are the most studied baths for the electrodeposition of copper alloy coatings 7,[11][12][13] . These compounds are non-toxic complexing agents, easily obtained and degraded 12,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the environmentally friendly electrolytes currently used, citrates, gluconates, sulfamates, tartrates and glycinates are the most studied baths for the electrodeposition of copper alloy coatings 7,[11][12][13] . These compounds are non-toxic complexing agents, easily obtained and degraded 12,14,15 . Previous works have shown that it is possible to obtain bright and uniform Cu-Zn and Cu-Co alloys coatings using environmentally favorable citrate and glycinate baths 4,6,10,13,16 .…”
Section: Introductionmentioning
confidence: 99%